Cryptochrome and quantum biology: unraveling the mysteries of plant magnetoreception - Thoradit, Thawatchai; Thongyoo, Kanjana; Kamoltheptawin, Khwanchai; Tunprasert, Lalin; El-Esawi, Mohamed A.; Aguida, Blanche; Jourdan, Nathalie; Buddhachat, Kittisak; Pooam, Marootpong (Frontiers in Plant Science, 2023)
Magnetoreception, the remarkable ability of organisms to perceive and respond to Earth's magnetic field, has captivated scientists for decades, particularly within the field of quantum biology. In the plant science, the exploration of the complicated interplay between quantum phenomena and classical biology in the context of plant magnetoreception has emerged as a n attractive area of research. This comprehensive review investigates into three prominent theoretical models: the Radical Pair Mechanism (RPM), the Level Crossing Mechanism (LCM), and the Magnetite-based MagR theory in plants. While examining the advantages, limitations, and challenges associated with each model, this review places a particular weight on the RPM, highlighting its well-established role of cryptochromes and in-vivo experiments on lightindependent plant magnetoreception. However, alternative mechanisms such as the LCM and the MagR theory are objectively presented as convincing perspectives that permit further investigation. To shed light on these theoretical frameworks, this review proposes experimental approaches including cutting-edge experimental techniques. By integrating these approaches, a comprehensive understanding of the complex mechanisms driving plant magnetoreception can be achieved, lending support to the fundamental principle in the RPM. In conclusion, this review provides a panoramic overview of plant magnetoreception, highlighting the exciting potential of quantum biology in unraveling the mysteries of magnetoreception. As researchers embark on this captivating scientific journey, the doors to deciphering the diverse mechanisms of magnetoreception in plants stand wide open, offering a profound exploration of nature's adaptations to environmental cues.